Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1080/10635150290102375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Models of Rate Evolution on Estimation of Divergence Dates with Special Reference to the Metazoan 18S Ribosomal RNA Phylogeny

Abstract: The molecular clock, i.e., constancy of the rate of evolution over time, is commonly assumed in estimating divergence dates. However, this assumption is often violated and has drastic effects on date estimation. Recently, a number of attempts have been made to relax the clock assumption. One approach is to use maximum likelihood, which assigns rates to branches and allows the estimation of both rates and times. An alternative is the Bayes approach, which models the change of the rate over time. A number of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(120 citation statements)
references
References 36 publications
2
116
0
2
Order By: Relevance
“…3 and 4) have suggested that the last common ancestor of bilaterians (LCB) lived well over one billion years ago (5, 6), whereas others suggest that LCB arose Ϸ900 million years ago (Ma) (e.g., refs. 7-10), and still others are more consistent with an origination closer to the Cambrian (11)(12)(13). These deep estimates for the origin of LCB raise the question of how hundreds of millions of years of bilaterian evolution can escape detection, given that LCB and its near relatives should have had the capability of leaving both body and trace fossils (14)(15)(16).…”
mentioning
confidence: 84%
“…3 and 4) have suggested that the last common ancestor of bilaterians (LCB) lived well over one billion years ago (5, 6), whereas others suggest that LCB arose Ϸ900 million years ago (Ma) (e.g., refs. 7-10), and still others are more consistent with an origination closer to the Cambrian (11)(12)(13). These deep estimates for the origin of LCB raise the question of how hundreds of millions of years of bilaterian evolution can escape detection, given that LCB and its near relatives should have had the capability of leaving both body and trace fossils (14)(15)(16).…”
mentioning
confidence: 84%
“…These values are substantially less than the ML distance (0.2) separating Trichuris muris from Trichuris suis. If the locus evolved in each lineage at Ϸ0.4 ϫ 10 Ϫ9 per site per year (4% over 100 MY), which typifies many metazoan phyla (9), then extant species of Trichinella shared a common ancestor Ϸ16 million years (MY) ago, and encapsulated taxa first began diversifying within the last 9 MY (Table 2). Only by postulating an implausible 18-fold rate decrease in divergence rate could the extant diversity among Trichinella species date to the origins of distinct tetrapod host groups that occurred some 300 MY B.P.…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches were considered for each data set to derive a temporal range. For SSU rDNA, a per-lineage calibration rate of 0.4 ϫ 10 Ϫ9 per site per year was assumed based on data generally supported for metazoan phyla (9). For mtDNA, data …”
Section: Methodsmentioning
confidence: 99%
“…[In the random rate case, the rate at each branch is randomly selected from a uniform distribution of rates so as to introduce a Ϯ40% random noise in evolutionary rate independently for each gene. In the correlated rate, the assignment of lineage-specific rate uses a stationary lognormal distribution in which the rates vary from branch to branch as a random walk for a given gene, so that rates drift up or down along the branches of any lineage (42,43). See Supporting Text.]…”
Section: Incorporating Multiple Fossil Bounds In the Bayesian Inferencementioning
confidence: 99%